2004
DOI: 10.1111/j.1532-7795.2004.01401001.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Self‐Consciousness: Longitudinal Age Changes and Gender Differences in Two Cohorts

Abstract: Adolescence is frequently described as a period of pervasive selfconsciousness, but an age-related peak in adolescence is not consistently obtained, and higher self-consciousness in girls is frequently obtained but not predicted by theoretical accounts. Two cohorts of adolescents (N 5 393), initially assessed at 13 and 15, completed public and private selfconsciousness measures 3 times in 4 years. They also reported social comparisons and social engagement. Public self-consciousness decreased and private self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 45 publications
6
113
1
Order By: Relevance
“…11,23,24 In a qualitative study of youth with CF, Willis et al 16 reported that girls who did not adhere to treatment were more likely to experience guilt compared to boys. This self-reflection about guilt is consistent with adolescent girls' greater private selfconsciousness, 17 which may be associated with more treatment discouragement, lower self-esteem 11,25 and poorer mental health reported for girls. 26 Conversely, poorer mental health is likely to lead to less adherence, creating a negative cycle between poor mental health and poor adherence.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…11,23,24 In a qualitative study of youth with CF, Willis et al 16 reported that girls who did not adhere to treatment were more likely to experience guilt compared to boys. This self-reflection about guilt is consistent with adolescent girls' greater private selfconsciousness, 17 which may be associated with more treatment discouragement, lower self-esteem 11,25 and poorer mental health reported for girls. 26 Conversely, poorer mental health is likely to lead to less adherence, creating a negative cycle between poor mental health and poor adherence.…”
Section: Introductionsupporting
confidence: 63%
“…These findings fit with observations that girls may be more attuned to how others perceive and respond to them and hence report greater strain when things are not going well. 17 Furthermore, in our earlier study, we found that parent-youth strain was directly linked to overall non-adherence for girls, but not for boys. 11 Although not directly measured, girls may experience more guilt when they are not adherent (as suggested by Willis et al 16 ), especially relative to their parents who likely are aware of and concerned about non-adherence; and these factors may contribute to emotional strain and worry.…”
Section: 7mentioning
confidence: 67%
See 2 more Smart Citations
“…They also explain why early adolescence is a time of heightened awareness of others' opinions, so much so that adolescents often engage in "imaginary audience" behavior, which involves having such a strong sense of self-consciousness that the teenager imagines that his or her behavior is the focus of everyone else's concern and attention. Feelings of self-consciousness increase during early adolescence, peak around age 15, and then decline (Ranking, Lane, Gibbons, & Gerrard, 2004). This rise and fall in self-consciousness has been attributed both to changes in hypothetical thinking (Elkind, 1967) and to fluctuations in social confidence (Ranking, Lane, Gibbons, & Gerrard, 2004), and although these may in fact be contributors to the phenomenon, the arousal of the socio-emotional network as a result of increases in pubertal hormones probably plays a role as well.…”
Section: Changes In Neural Oxytocin At Pubertymentioning
confidence: 99%